2017
DOI: 10.1016/j.biortech.2017.07.082
|View full text |Cite
|
Sign up to set email alerts
|

Biochar modification to enhance sorption of inorganics from water

Abstract: Biochar can be used as a sorbent to remove inorganic pollutants from water but the efficiency of sorption can be improved by activation or modification. This review evaluates various methods to increase the sorption efficiency of biochar including activation with steam, acids and bases and the production of biochar-based composites with metal oxides, carbonaceous materials, clays, organic compounds, and biofilms. We describe the approaches, and explain how each modification alters the sorption capacity. Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
187
1
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 578 publications
(213 citation statements)
references
References 100 publications
3
187
1
22
Order By: Relevance
“…Damaging fish spawning, affecting aquatic environment of insects and fishes [20] Inorganic Pollutants Metals compounds, Trace elements, Inorganic salts, Heavy metals, Mineral acids, Aquatic flora and fauna, Public Health problems [21] Organic Pollutants Detergents, Insecticides, Herbicides.…”
Section: Water Pollutants Source Of Pollutants Effect Of Pollutants Rmentioning
confidence: 99%
“…Damaging fish spawning, affecting aquatic environment of insects and fishes [20] Inorganic Pollutants Metals compounds, Trace elements, Inorganic salts, Heavy metals, Mineral acids, Aquatic flora and fauna, Public Health problems [21] Organic Pollutants Detergents, Insecticides, Herbicides.…”
Section: Water Pollutants Source Of Pollutants Effect Of Pollutants Rmentioning
confidence: 99%
“…As shown in Fig. 3, mechanistic pathways for metal immobilization using biochar can be explained by altering the pH of the soil to increase/induce ionic exchange, surface adsorption, and possible precipitation, and generally improving soil properties (Bernal et al 2006;Gomez-Eyles et al 2013a, b;Sizmur et al 2017). Biochar is also reported to contain sufficient surface area due to the wide distribution of microor mesopores.…”
Section: Potential Mechanism Of Heavy Metal Remediation By Biocharmentioning
confidence: 99%
“…Biochar is also reported to contain sufficient surface area due to the wide distribution of microor mesopores. It is reported that increases in the amount of micropores increase the ability of surface area and surface sites on which metals can quickly attach (Sizmur et al 2017). Furthermore, the reason for the removal of Cr is the ability of biochar to complex and electrostatically interact with heavy metals, wherein contamination of Cd and Pb is controlled by cation exchange and precipitation, while that of Hg is due to reduction and complexation (Li et al 2017;Rajapaksha et al 2016).…”
Section: Potential Mechanism Of Heavy Metal Remediation By Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar can be obtained by vegetable or animal biomass residues, as industrial and agricultural wastes. This carbon-rich material present a highly porous and functionalized surface which promotes an effective interaction with organic and inorganic species [25]. The chemical activation of this material can promotes a significant increase of surface active sites improving its sorption capacity [26].…”
Section: Introductionmentioning
confidence: 99%